Circadian variation of mean pressure: rate product (mPRP) in patients with hypertension.------6th report - Lau, Alan HC; Takeshita, Moriyuki (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1993)
The aim of this study was to investigate the clinical usefulness of mean pressure-rate product (mPRP) in managing hypertension. The assessment of the differences between normotensive and hypertensive subjects in the circadian variation of mPRP by sex and age was performed. Ambulatory blood pressure monitoring (ABPM) based (TM 2420) measurements were satisfactorily performed on 824 outpatients aged 30-89 years. These included 206 normotensives (NT), 212 non-treated hypertensives (NTH) and 406 treated hypertensives (THT). All subjects were classified into two groups according to age-30 to 59 years of age (younger group) and 60 to 89 years of age (older group). Blood pressure and heart rate were obtained at half or one hour intervals from 6 : 00-18 : 00 and one hour intervals from 18 : 00-6 : 00. Circadian variation was divided into diurnal variation : 6 : 00-12 : 00 and 12 : 00-18 : 00 and nocturnal variation : 18 : 00-24 : 00 and 24 : 00-6 00. Base blood pressure and heart rate were obtained as the bottom blood pressure and heart rate throughout 24 hours. By using the ABPM, all patients were asked to check their own basal blood pressure under metabolic condition and also blood pressure while awake upon attaining the initial standing position in the early morning and the heart rates were recorded automatically. Casual blood pressure (CBP) were measured by conventional ausculatory method with a mercury sphygmomanometer. The following results were obtained : 1) Mean values of casual mPRP for cases in NHT and THT were significantly higher compared to cases in NT for groups in both sexes and ages. The mean values of casual mPRP for cases in NHT were also significantly higher compared to cases in THT for both sexes in the older groups. 2) Mean values of basal mPRP for cases in NT were never below 5, 000, whereas the corresponding figures for cases in NHT. and THT were never below 6, 000 in cases for groups in both sexes and ages. 3) The ranges of circadian variations of mPRP were 8, 000 to 4, 000 in almost all cases in NT, whereas the corresponding figures were 9, 000 to 5, 000 in most cases in NHT and 8, 000 to 4, 000 in most cases in THT respectively. Since the values of basal mPRP and the ranges of circadian variations of mPRP between NT, NHT and THT were obviously different, it is concluded that the values and the circadian variation of mPRP are useful parameters in managing hypertension.